2015
DOI: 10.3748/wjg.v21.i14.4210
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton microscopy for tumor regression grading after neoadjuvant treatment for colorectal carcinoma

Abstract: MPM can be used to perform real-time diagnosis of tumor response after neoadjuvant treatment, and can be applied to evaluate TRG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Nonlinear optical microscopy has been extensively used for the diagnosis of cancer diseases based on specific estimating parameters, which are tabulated in Table 2 as an overview on the existing applications. Among them, the intensity ratio of TPEF/SHG has been used to differentiate between cancerous and normal tissues; 15,17,27,28 however, to our knowledge, this approach has not previously been used for the staging of ESCC. Here we investigated the single collagen fibers in submucosa of cancerous tissues and counted the intensities of TPEF and SHG for ratiometric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nonlinear optical microscopy has been extensively used for the diagnosis of cancer diseases based on specific estimating parameters, which are tabulated in Table 2 as an overview on the existing applications. Among them, the intensity ratio of TPEF/SHG has been used to differentiate between cancerous and normal tissues; 15,17,27,28 however, to our knowledge, this approach has not previously been used for the staging of ESCC. Here we investigated the single collagen fibers in submucosa of cancerous tissues and counted the intensities of TPEF and SHG for ratiometric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic contrast enhanced MRI and positron emission tomography may be valuable to evaluate the response of CRT . A recent study showed that multiphoton microscopy could be used to perform real‐time diagnosis of tumour response for colorectal cancer after neoadjuvant treatment . Microarray gene expression analysis suggested a gene set comprising the top‐ranked 95 genes to predict complete response to CRT .…”
Section: Discussionmentioning
confidence: 99%
“…The radiation-induced changes of normal rectum tissue such as degradation and subsequent remodeling of collagen also can be estimated by using SHG imaging [31]. The extent of stromal fibrosis and observation of residual tumors after neoadjuvant radiochemotherapy can be established to distinguish tumor regression grading of colorectal adenocarcinomas treated with neoadjuvant therapy (figure 3) [32].…”
Section: Evaluating Colorectal Cancer Therapy Responsementioning
confidence: 99%
“…Scale bar: 100 µm. Adapted from [32]. multiphoton absorption has also been used as a useful tool for the selective ablation of tissue structures.…”
Section: Visualizing and Ablating Pre-invasive Colorectal Cancer Cellsmentioning
confidence: 99%